NEW PARADIGMS IN THE RESEARCH ON ANTECEDENTS OF EMPLOYEE ENGAGEMENT: DRAWING EVIDENCE FROM THE LATEST LITERATURE (International Journal of Food and Nutritional Sciences, 2022)
Employee engagement is a dominant issue, especially in the present day. The global level of employee engagement at 15%, which means 85% of employees worldwide are not engaged(Jouany & Mäkipää, 2022). Multiple factors that may increase employee engagement are under investigation by corporations and scholars. Strategies must undergo constant modification to suit the corporate environment's adaptability. There have been substantial changes in the manner in which businesses operate. The pandemic, economic crisis, and political turmoil, among other factors, have all impacted company operations. In this study, an attempt is made to examine recent employee engagement trends using the most current research available. The research articles are selected from 2020 to 2022 from reputed journals. The methodology used is the theory synthesis of (Jaakkola, 2020), as it integrates concepts through various theories and available literature. About twenty-five constructs or variables were identified during the review as antecedents of employee engagement. It was found that the researchers have explored various contemporary variables which impact employee engagement. However, the author has reviewed the paradigm shift in employee engagement research, identified specific gaps, and suggested a few probable predictors of employee engagement that future researchers can investigate.